Design and discovery of C2-fluoroalkyl iminothiazine dioxides as BACE inhibitors. (15th January 2022) - Taoka, Brandon M.; Wu, Wen-Lian; Hao, Jinsong; Dolmaski, Martin; Wang, Hongwu; Levorse, Dorothy; Orth, Peter; Hyde, Lynn A.; Smith, Brad; Michener, Maria S.; Kennedy, Matthew E.; Parker, Eric M.; et al.
Graphical abstract: Abstract: This paper describes the structure–activity-relationships of novel fluoroalkyl substituents at the C2 position of iminothiazine dioxide beta secretase inhibitors. Key discoveries include reduced amidine basicity and its effect on Pgp, cell potency, and efficacy in various preclinical in vivo efficacy animal models. Findings from these structure–activity-relationships are discussed.